ASSIMPTOMATIC BACTERIURIA OF PREGNANCY, DIAGNOSTICS AND EXPERIENCE OF TREATMENT IN THE HEALTH CENTER IN OMSK - Сатыбалдин, Данияр Агыбаевич; Кравченко, Елена Николаевна; Вотрина, Ирина Рахимжановна (Mother and Baby in Kuzbass, 2018)
Asymptomatic bacteriuria, according to different authors, occurs in 2-22 % of pregnant women and, in the absence of treatment, in 30 % is complicated by the development of gestational pyelonephritis, and is also associated with the development of severe complications of pregnancies and childbirth. Effective diagnosis and treatment leads to a significant reduction in the incidence of these complications. A single dose of phosphomycin is as effective as the course of antibiotic therapy.